The results of prosthetic plasty of the anterior abdominal wall at the treatment of postoperative ventral hernias - K. V. Shevschenko; A. V. Shcherbatykh; S. V. Sokolova (Acta Biomedica Scientifica, 2014)
We studied the results of treatment of 167 patients with postoperative ventral hernias (POVH) with use of mesh endoprosthesis. Basic group included 22 (13,0 ± 2,6 %) patients, who had plasty of anterior abdominal wall with use of proposed method. This method is a modification of «on lay» plasty. The first group of clinical comparison included 95 (57,0 ± 3,8 %) patients operated with «on lay» method. The second group of clinical comparison included 50 (30,0 ± 3,5 %) patients operated with «sub lay» method. Morphological study of hernial sac was conducted, the indications to the new method of plasty were revealed, its efficiency in comparison with «on lay» plasty was proved. The article reviews frequency and character of complications and quality of life of patients after application of various kinds of prosthetic plasty. We developed an algorithm for choosing the method of abdominal wall plasty.